2020
DOI: 10.2147/jbm.s263327
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Anemia and Its Associated Factors Among Female Adolescents in Ambo Town, West Shewa, Ethiopia</p>

Abstract: Objective This study assessed the prevalence of anemia among female adolescents and factors associated with it in Ambo town, West Shewa, Ethiopia. Materials and Methods A community-based cross-sectional study was conducted among 523 randomly selected female adolescents living in Ambo town, Ethiopia from August 5–29, 2018. Data were collected through structured interview using a structured questionnaire. Anthropometric measurements were done and the hemoglobin value was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 17 publications
5
24
1
2
Order By: Relevance
“…The finding of this study indicated that anemia is a major public health problem among young women according to the WHO classification of anemia for public health significance. Anemia prevalence among young women was higher than the studies conducted in Ethiopia, East Africa, Rwanda, Nepal and Chinese [ 12 , 25 , 27 33 ]. Meanwhile, the pooled prevalence of anemia in this study was lower than the prevalence reported in Ghana [ 34 ], Cameron [ 34 ], Congo democratic republic [ 34 ], Burkina Faso [ 34 ] and Asia [ 22 ].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The finding of this study indicated that anemia is a major public health problem among young women according to the WHO classification of anemia for public health significance. Anemia prevalence among young women was higher than the studies conducted in Ethiopia, East Africa, Rwanda, Nepal and Chinese [ 12 , 25 , 27 33 ]. Meanwhile, the pooled prevalence of anemia in this study was lower than the prevalence reported in Ghana [ 34 ], Cameron [ 34 ], Congo democratic republic [ 34 ], Burkina Faso [ 34 ] and Asia [ 22 ].…”
Section: Discussioncontrasting
confidence: 56%
“…It also results in stunted child development, impaired learning and decreased work efficiency [ 10 , 11 ]. Anemia harms the health of women in reproductive age and pregnant women, under-five and preschool children, adolescents and young women [ 6 , 9 , 12 15 ]. Besides, the increased burden of anemia among adolescent and young women is associated with a period of rapid physical growth, reproductive maturation and cognitive transformations, which leads to higher demands for macro and micronutrients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding is comparable to previous studies conducted in Southern and Northwest Ethiopia [ 22 , 23 ]. However, the prevalence is comparatively lower than studies done in different parts of Ethiopia such as Ambo Town, West Shewa which reported a prevalence as high as 39% [ 24 ]; 29% prevalence among school adolescents from Haramaya, Eastern Ethiopia [ 25 ] and 27% from southwest rural Ethiopia [ 26 ]. The potential reason for this discrepancy could be the target population, geographical area and sample size variations.…”
Section: Discussionmentioning
confidence: 91%
“…[ 4 ] in North West Ethiopia, Tura MR et al . [ 25 ] in West Shewa, Ethiopia and Fentie K et al . [ 26 ] in Southwest Ethiopia.…”
Section: Discussionmentioning
confidence: 99%